Methodology of Political Science. The case of Eurasianism - Bäcker, Roman (Wydawnictwo Naukowe WNPiD UAM, 2019)
The text answers the following question: what is the point of conducting political science research? The research can make a lot of sense when you are strongly motivated and, motivation is just as important as your knowledge how to do it. In the latter case, you must proceed in the correct order. Firstly, the boundaries of the research field should be set, and secondly, original and unconventional research problems and hypotheses should be defined. Thirdly, the proper selection of primary and secondary sources is necessary. Fourthly, you choose appropriate research methods and techniques, and then construct a research tool or tools. After the determining of the level of accuracy and relevance of data collected, it is possible to proceed to the verification of hypotheses. The more thorough the process and the more inquisitive researcher, the more interesting research results are obtained.

Tekst odpowiada na pytanie: jaki jest sens prowadzenia badań politologicznych? Wtedy, gdy ma się odpowiednią motywację i (co równie ważne) wie się, jak to można zrobić. W tym drugim przypadku musi się postępować w odpowiedniej kolejności. Po pierwsze, należy wyznaczyć granice pola badawczego, a po drugie, określić oryginalne, niebanalne problemy i hipotezy badawcze. Po trzecie, konieczny jest odpowiedni dobór i sposób selekcji źródeł pierwotnych i ewentualnie wtórnych. Czwartym etapem jest dobranie adekwatnych metod i technik badawczych, a następnie skonstruowanie narzędzia lub narzędzi badawczych. Po określeniu poziomu prawdziwości i stosowalności zebranych informacji możliwe jest dopiero przystąpienie do weryfikacji hipotez. Im bardziej ten ostatni proces będzie rzetelny, a badacz dociekliwy, tym ciekawsze uzyska się rezultaty badawcze.
Metodologia badań politologicznych na przykładzie eurazjatyzmu
Keywords: methodology; research methods and techniques; Eurasianism; metodologia; metody i techniki badawcze; eurazjatyzm